Performance of Secure Framework AES Algorithm using Cloud Computing - Rani, R.; Bathla, R. K. (Journal of Scientific Research, 2024)
The conventional advanced encryption standard (AES) method requires improvement to accommodate modern security hazards in cloud computing. Outsourcing private and secret information to distant information networks is difficult due to new problems connected with the confidentiality and safety of information. The structure presented by this study has essential components involving improved security and owner-data privacy. The dual-cycle key attribute alters the 128-bit AES method, accelerating encryption at 1000 bits per second. However, a singular circular bar with 800 blocks per second has been used historically. The suggested technique uses less energy and improves the distribution of load, trust, and control of resources on the entire network. The proposed framework calls for the use of AES with 128, 64, 32, and 16 bytes of simple text. Visualizing simulation outcomes shows the technique's capability for obtaining specific quality features. According to the assessments, the proposed framework reduces energy consumption by 14.43 %, connection utilization by 11.53 %, and delay by 15.67 %. As a result, the suggested framework improves protection, decreases resource usage, and shortens latency when delivering computing services over the cloud. The experiment was done with Anaconda Python and Eclipse.